2021
DOI: 10.1038/s41598-020-80375-1
|View full text |Cite
|
Sign up to set email alerts
|

Electric field assisted motion of a mercury droplet

Abstract: Field-assisted self-assembly, motion, and manipulation of droplets have gained much attention in the past decades. We exhibit an electric field manipulation of the motion of a liquid metal (mercury) droplet submerged in a conductive liquid medium (a solution of sulfuric acid). A mercury droplet moves toward the cathode and its path selection is always given by the steepest descent of the local electric field potential. Utilizing this unique behavior, we present several examples of droplet motions, including ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…An additional application of liquid metal actuation is powering the movement of the robot boat by the continuous electrowetting approach . Another interesting aspect is that liquid metal droplets are able to solve complicated mazes due to the application of the electrochemical driving force and the fact that the liquid metal always moves toward the steepest decent of the local electrical field potential. , …”
Section: Surface Tensionmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional application of liquid metal actuation is powering the movement of the robot boat by the continuous electrowetting approach . Another interesting aspect is that liquid metal droplets are able to solve complicated mazes due to the application of the electrochemical driving force and the fact that the liquid metal always moves toward the steepest decent of the local electrical field potential. , …”
Section: Surface Tensionmentioning
confidence: 99%
“…128 Another interesting aspect is that liquid metal droplets are able to solve complicated mazes due to the application of the electrochemical driving force and the fact that the liquid metal always moves toward the steepest decent of the local electrical field potential. 129,130 By directly applying a potential to the liquid metal, the interfacial tension of the liquid metal can be altered substantially (between around 500 mN/m to below 50 mN/ m). This can be exploited for controlled deformation of the liquid metal.…”
Section: T T T Tmentioning
confidence: 99%
“…In a related work, Čejková et al 10 found that a gradient in salt concentration could drive the translational motion of alcohol droplets in an aqueous solution of sodium decanoate. Manipulation of the motion of a mercury droplet submerged in a conductive liquid medium by using a direct electric field was studied by Hollo et al 11 . The electric potential drop across the droplet was found to generate Marangoni flow within the liquid which drives the droplet to move towards the cathode.…”
Section: Introductionmentioning
confidence: 99%
“…One is the asymmetry incorporated in the system, like the asymmetric position of camphor grains on a boat 14 or a gradient patterned artificially into the environment. [15][16][17] An example of the latter is artificial chemotaxis which has been intensively studied. 12,[18][19][20][21][22][23][24][25][26] Such surfers are propelled by a chemical gradient, where the symmetry is already broken thus making the self-propulsion stable and predetermined in a directional sense.…”
Section: Introductionmentioning
confidence: 99%